Peningkatan kompetensi guru melalui pelatihan media video di Kabupaten Sinjai - Nurhikmah H; Abd. Haling (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The benefits of video media in education are able to increase students interest in learning because students can listenand see pictures. Teachers are expected to design an innovative, creative, efficient and effective learning media that can enhancethe active learners in the learning process. Malasalah found between 1) teachers ability is still low in the production of their ownlearning media mainly in making learning videos, 2) Availability of free software that can be used to produce learning videomedia But never utilized by teachers, 3) improved teaching and learning process is effective, efficient, and more interesting.Overcoming the problem is take steps to conduct training with a variety of lecture methods that are divided into three phases:planning, implementation and evaluation. The external result of this activity is 1) the availability of video editing applications 2)Guru has been able to use video editing application, and 3) product produced by the teacher.